Comparative Study between the Behavior of the Concrete Thrust Block and the Restraint Joint in a Water Distribution System; Review (Journal of Engineering, 2022)
Thrust blocks and restraint joints are the two most popular methods of counteracting the thrust force that generated at pipe fittings (bends, Tee, wye, reducers, dead ends, etc…). Both systems perform the same function, which is to prevent the joints from separating from the pipes. The aim of the study is to review previous studies and scientific theories related to the study and design of thrust blocks and restraint joints to study the behavior of both systems under thrust force and to study the factors and variables that affect the behavior of these systems. The behavior of both systems must be studied because they cannot be abandoned, as each system has conditions whose use is more feasible, scientific, and economical. The use of thrust blocks is usually more economical. Still, in many cases, its use is not appropriate, as it is required to wait for the result of the compressive strength test of the concrete. It is required to close the pipe trench as soon as possible; thus, this affects the safety of workers. Or there are future excavation works that may harm the stability of the block, and when the pipe diameter is large, we need a large amount of concrete which affects the economic aspect of the work. For this, the alternative system (restraint joint) must be studied. The main result of the research is that each system provides the opposite force against thrust force with a different mechanism from the other depending on the properties of the soil.